Self-assembly of supramolecular complexes of charged conjugated polymers and imidazolium-based ionic liquid crystals. (March 2022) - Zhang, Shanju; Beach, Evan; Anastas, Paul T.; Pfefferle, Lisa D.; Osuji, Chinedum O.
Abstract: The use of supramolecular interactions to construct mesogens represents a versatile means of accessing new macromolecular architectures, and material properties in the resulting mesophases. Here, we demonstrate the formation of thermotropic liquid crystalline supramolecular conjugates of sulfonated poly(alkyl thiophenes) backbones coupled to biphenyl-containing 1-alkyl-3-methylimidazolium salts with bromide counter anions. Two types of liquid crystalline imidazolium salts are studied with chemical structures differing in the terminal group of the biphenyl mesogenic unit. Both ionic liquid crystals exhibit multiple phase transitions with lamellar structures, which correspond to crystal and smectic liquid crystalline transitions. Supramolecular complexes of sulfonated polythiophene and ionic liquid crystals display thermotropic liquid crystalline phases with lamellar-like nanostructures. Detailed analysis show that the lamellar periodicity increases in the supramolecular complexes, compared to those of the ionic liquid crystals. Aligned textures were produced in thin films of supramolecular complexes by shear and magnetic field alignment of the liquid crystalline mesophases. The incorporation of ionic liquid crystal units into a conjugated polymer opens opportunities for fabrication of aligned thin films of mixed electron-ion conducting polymers. Such molecular materials could be of interest in electrochemical devices. Graphical abstract: Image, graphical abstract Electrostatic interactions are used to construct supramolecular mesogens consisting of ionic mesogens complexed with a complementary charged conjugated polymer. The resulting systems show thermotropic self-assembly and are readily aligned using magnetic fields and shear flow. These systems are potentially useful for simultaneous electronic and ionic charge transport.